2019
DOI: 10.26905/jmdk.v7i2.3830
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kebijakan Pemerintah dalam Memperkuat Aliansi Strategis dan Meningkatkan Daya Saing Ekonomi Kreatif

Abstract: This study aims :1) to examine the effect of strategic alliances and government policies on the achievement of competitive advantage of micro, small and medium creative enterprises, 2) to assess the role of government policies in moderating the relationship between strategic alliances and competitive advantage. This study was conducted in 130 micro, small and medium craft enterprises in Malang Raya. Using SEM-PLS in WarpPLS 6.0, this study finds that strategic alliances have significant effects on competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…In previous studies, the research was more focused on the policy side of business success in obtaining business permits and government funding schemes (Khouroh et al, 2019). In addition, previous research has shown that the government's role in assisting the business world is very much needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the research was more focused on the policy side of business success in obtaining business permits and government funding schemes (Khouroh et al, 2019). In addition, previous research has shown that the government's role in assisting the business world is very much needed.…”
Section: Resultsmentioning
confidence: 99%
“…Four roles can be taken by local government, namelyas an entrepreneur, the local government is responsible for running a business; As a coordinator, local governments can act as coordinators to create policies. Policies that lead to business success is the convenience to get a business license and government scheme funding (Khouroh et al, 2019). Industrial policy is defined as the use of power and government resources to implement a policy to meet the needs of a particular sector or industry (Saing et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Kelembagaan masyarakat yang mengembangkan usaha tani berusaha mengentaskan kemiskinan dan mencapai taraf hidup yang lebih baik. Upaya-upaya tersebut, ditempuh melalui pengembangan ekonomi berkelanjutan yang dapat menghadapi sejumlah kendala seperti kekurangan modal, rendahnya daya saing, kurangnya tata kelola managemen, sulitnya akses pemasaran, dan kurangnya jaringan maupun informasi (Khouroh et al, 2019). Berdasarkan persoalan tersebut, maka pengembangan KWT Tuwuh Makmur dalam pemberdayaan di Dukuh Santren mulai membina tentang proses wirausaha sebagai bentuk ketahanan pangan dan kebutuhan masyarakat.…”
Section: Pendahuluanunclassified
“…Kolaborasi dan aliansi dengan sektor lain memberikan ruang untuk berbagi pengetahuan, pelatihan, memberikan peluang baru dan hal-hal lain yang sangat penting bagi kelangsungan dan keberlanjutan UMKM (Khouroh et al, 2019;Beaver & Hutchings, 2005). Selanjutnya, dalam situasi "krisis", integrasi kegiatan pelatihan dan pengembangan ke dalam keputusan dan kegiatan bisnis yang kritis dapat menjadi alat untuk memecahkan masalah yang dihadapi perusahaan.…”
Section: Pemerintah Industri Akademikunclassified